Sosialisasi Pemanfaatan Limbah Pecahan Genteng sebagai Agregat Kasar Alternatif dalam Konstruksi Ringan - Reynold Andika Pratama; Era Agita Kabdiyono; Hidayat Dwi Saputra; Acep Enang Supriatna; Muhamad Febriansyah (Asosiasi Dosen Muda Indonesia, 2026)
The increasing volume of construction waste, particularly broken roof tile debris, has become an environmental concern that requires innovative and sustainable solutions. This Community Service Program (PKM) aimed to socialize and introduce the utilization of roof tile fragment waste as an alternative coarse aggregate in lightweight construction to the local community. The activity was conducted through educational seminars, discussions, and practical demonstrations involving community members and construction practitioners. The program emphasized the potential benefits of recycled roof tile waste, including waste reduction, environmental preservation, and cost efficiency in construction materials. The results of the socialization activities indicated that participants gained a better understanding of sustainable construction practices and showed positive responses toward the application of roof tile waste as an alternative material in lightweight concrete and non-structural construction components. Furthermore, the program encouraged community awareness regarding the importance of recycling construction waste into value-added materials. Therefore, the utilization of broken roof tile waste as alternative coarse aggregate can serve as an environmentally friendly and economically beneficial solution for sustainable lightweight construction development.